Functions and management skills counter - Madruga, Sergio Rossi; Colossi, Nelson; Biazus, Cleber Augusto (Revista de Administração da UFSM, 2016)
The profile of the professional accounting changed because, increasingly, new skills are required to Accounting Bachelor. This professional has to have duties and responsibilities different from those that until then determined their functions and their position in the company. Their participation in decision-making has required you a broader view of the scenarios in which your company operates and their work is no longer just an operational tool transcription values and financial results, which led to the need to take, too, management functions. Thus, this study aims to raise some conceptual aspects of managing, in order to emphasize the relevance of research related to training in higher education Counter. Methodologically, this article constitutes a qualitative approach in an attempt to show the conceptual proximity and interaction between Counters and Administrators. For this, we tried to identify, descriptively, the relationships between variables and understand the analogy profiles and skills necessary for professional training in the areas of administration and accounting, closely linked in the corporate world. The results show that the new professional profile required by the market Counter, making it necessary to adopt some key features and innovative trends such as entrepreneurship and decision making, capacity for discernment and critical thinking to judge and choose alternatives and ethical conduct associated with social and professional responsibility.